MENTAL HEALTH AND THE GOSPEL: A RESPONSE TO CHRISTOPHER COOK: with Christopher C. H. Cook, "Mental Health and the Gospel: Boyle Lecture 2020"; and Fraser Watts, "Mental Health and the Gospel: A Response to Christopher Cook.". Issue 4 (1st October 2020) - Watts, Fraser
Abstract: It is sometimes assumed that when the gospels talk about demon possession they are just using different terminology for what would now be called psychosis or epilepsy. However, these terms come from different discourses that need to be distinguished, but do not need to be kept completely separate. The nature of the relationship between religion and mental health is complex. There is usually a positive correlation, but it is more difficult to be confident about the nature of the causal connection. Poor mental health can become intertwined with religion in a way that drags both down. It is a consistent feature of Jesus' interactions that he encourages people to believe that more is possible than might have been imagined. His impact on the mental health of those around him seems to have been largely a matter of what might now be called positive psychology.